ANALISIS ZONASI KAWASAN RESAPAN AIR DI KECAMATAN KWANDANG KABUPATEN GORONTALO UTARA - Antule III, Andri Darmawan (Universitas Bina Taruna Gorontalo, 2023)
The research aims to determine the zoning of water catchment areas in Kwandang District and find out how appropriate the use of regional spatial planning is in water catchment areas in Kwandang District. This research emphasizes a spatial approach. Analyze the variables to be studied using the overlay method with Geographic Information System (GIS) software and data scoring to identify water catchment areas. The zoning of water catchment areas in Kwandang District can be divided based on the classification of natural infiltration potential, namely large, medium and small natural infiltration potential. Medium natural infiltration potential has the largest area of around 17375.17 Ha or 88.61% of the total water catchment area, large natural infiltration potential has an area of 2201.21 Ha or around 11.23%, while small infiltration potential has the smallest area, namely 31.64 Ha or around 0.16% of the water catchment area in Kwandang District. Water catchment areas that have small and moderate natural infiltration in terms of space use can be used for the construction and development of cultivation areas, while water catchment areas that have large natural infiltration are recommended for use of space as protected areas. Keyword: Zoning; Water infiltration; Kwandang district.